2018
DOI: 10.1371/journal.pone.0204911
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokine oncostatin M induces endothelial activation in macro- and microvascular endothelial cells and in APOE*3Leiden.CETP mice

Abstract: AimsEndothelial activation is involved in many chronic inflammatory diseases, such as atherosclerosis, and is often initiated by cytokines. Oncostatin M (OSM) is a relatively unknown cytokine that has been suggested to play a role in both endothelial activation and atherosclerosis. We comprehensively investigated the effect of OSM on endothelial cell activation from different vascular beds and in APOE*3Leiden.CETP mice.Methods and resultsHuman umbilical vein endothelial cells, human aortic endothelial cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 66 publications
6
21
0
1
Order By: Relevance
“…This cytokine is secreted by activated macrophages and neutrophils and signals through the Leukemia Inhibitory Factor Receptor (LIFR) and the OSM receptor (OSMR)[5–7]. OSM induces endothelial activation by increasing cytokine release, adhesion molecule expression, and leukocyte adhesion to the activated endothelium in cultured endothelial cells[8–10]. Moreover, OSM reduces vascular integrity of rat blood brain barrier endothelial cells and enhances angiogenesis[11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cytokine is secreted by activated macrophages and neutrophils and signals through the Leukemia Inhibitory Factor Receptor (LIFR) and the OSM receptor (OSMR)[5–7]. OSM induces endothelial activation by increasing cytokine release, adhesion molecule expression, and leukocyte adhesion to the activated endothelium in cultured endothelial cells[8–10]. Moreover, OSM reduces vascular integrity of rat blood brain barrier endothelial cells and enhances angiogenesis[11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Using a different approach, we recently demonstrated that short-term OSM administration (for 3 weeks) to APOE*3Leiden.CETP mice increased plasma E-selectin levels, Interleukin (IL)-6 mRNA expression in the aorta and Intercellular Adhesion Molecule 1 (ICAM-1) expression and monocyte adherence to the activated endothelium in the aortic root[10]. Collectively, these findings suggest that OSM may be involved in atherosclerosis development but so far this has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…By activating the JAK/STAT pathways, it affects cell growth, neuron development, the inflammatory response, and other physiological process (6,7). OSM signals via the LIF receptor-alfa (LIFR) and OSM receptor (OSMR) (8). OSM and the OSMR are potential therapeutic targets in chronic inflammatory diseases that cause endothelial dysfunction, such as rheumatoid arthritis, atherosclerosis, thrombosis, and abnormal angiogenesis (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…OSM has been characterized as an angiogenic factor [58], and acts on vascular endothelial cells in a pro-inflammatory manner [59,60]. These studies were completed in aortic vascular endothelial cells, but whether pulmonary vasculature endothelial cells respond in the same manner is not clear at this time.…”
Section: Vascular Endothelial Growth Factor (Vegf) and Prostaglandin Ementioning
confidence: 99%